Associations of retinal microvascular caliber with intermediate phenotypes of large arterial function and structure: A systematic review and meta‐analysis. (10th July 2019) - Liu, Mengjiao; Wake, Melissa; Wong, Tien Yin; He, Mingguang; Xiao, Yinzong; Burgner, David P.; Lycett, Kate
Abstract: Objective: Intermediate phenotypes of microcirculation (retinal microvascular caliber) are associated with cardiovascular (CV) risk factors and independently predict CV events. However, the effect of microcirculation variation on the vascular system is unclear. We conducted a systematic review and meta‐analysis of observational studies to quantify associations of retinal microvascular caliber (arteriolar, venular caliber, arteriole‐to‐venule ratio) and preclinical CV measures (large arterial function and structure). Methods: We identified studies in MEDLINE, EMBASE, and PubMed (1946 to March 2018) studying (a) general population samples and (b) patients with cardiometabolic disease. Study‐specific correlation estimates were combined into meta‐analysis where possible. Results: Of 1294 studies identified, 26 met inclusion criteria (general population 16, patients 10), of which five studies were included in meta‐analysis. Most studied middle‐aged adults cross‐sectionally, with one childhood study. Large arterial function and structure were predominantly assessed by pulse wave velocity and carotid intima‐media thickness, respectively. Only arteriolar caliber was consistently associated with arterial function and structure, with stronger associations observed in cardiometabolic patients. Narrower (worse) arteriolar caliber was associated with faster (poorer) pulse wave velocity (correlation coefficient ( r ) −0.17, 95% CI −0.25 to −0.10) and greater (poorer) intima‐media thickness ( r −0.05, 95%CI −0.09 to −0.02) across all adult participants. Conclusions: Retinal arteriolar, but not venular caliber, was modestly associated with large arterial function and weakly associated with large arterial structure, with stronger evidence in patients with cardiometabolic disease. This suggests that preclinical changes in large arteries and the microcirculation have some shared but mainly unique pathways to associate with cardiovascular disease.